Pragmatic Functions of Yobikake Kandōshi Used by the Character Haruka Sakura in the Anime Wind Breaker - Rahayu, Anggi Septiani; Arianingsih, Anisa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The purpose of this research is to examine the use of Yobikake Kandōshi in the dialogue of Haruka Sakura in the anime Wind Breaker. Kandōshi is an interjection of Japanese origin that is used to convey emotions, responses, and/or calls to the interlocutors in a communication process. The purpose of this research is to identify the forms of Yobikake Kandōshi used by Haruka Sakura and analyze the pragmatic use of Kandōshi based on the context of the utterances. The research method of this study is qualitative research using a descriptive method. The data source of this research is the dialogue of Haruka Sakura in the anime Wind Breaker, particularly episodes 1-5. The data collection method of this research is the observation method by applying Simak Bebas Libat Cakap (SBLC) techniques and note-taking. The data analysis method of this research is based on Yule’s (1996) pragmatic theory and Leech’s (1993) speech situation framework. The results of the research showed that three forms of Yobikake Kandōshi are used by Haruka Sakura in her dialogue in the anime Wind Breaker. The three forms of Kandōshi are oi, hora, and yo. The most dominant form of Kandōshi is oi, which is used to attract the attention of the interlocutors in an informal communication process. Yobikake Kandōshi also have several pragmatic functions, such as expressing annoyance, giving commands, asking for explanations, greeting the interlocutors, and provoking opponents in a confrontational communication process. The use of Yobikake Kandōshi indicates that Kandōshi is not only an attention-getting device but also a significant device for the expression of the attitude and emotions of the speaker in a communication process.